PENANGANAN LOSS JARINGAN INTERNET PADA PERANGKAT ODP di WITEL KARAWANG - Akhmad Auliya Fatahilah; Lela Nurpulaela (Power Elektronik : Jurnal Orang Elektro, 2021)
Abstract  This writing is made to find out the mass disturbances that occur in the fiber coverage area in the region, this is because there are several factors caused by malfunctions of several optical devices that distribute internet networks to customers. The occurrence of loss of internet network on devices in the work area of Karawang greatly affects the activities of customers at home in Karawang. So that the decrease in the quality of internet speed occurs and some customers have their internet network disconnected. In this article, we will discuss the procedures for handling when an internet network loss occurs and some anticipatory steps when the malfunction occurs. Occurrence of optical loss interference because the level of high attenuation exceeds the threshold 27 dBm. The division of each core for each ODP is 8 to 12 cores. With more load on this core which makes a distribution that is less than optimal. Power levels on ODC devices range from -4 to -6 dBm.